Human immune deficiency virus among cervical cancer patients at Tikur Anbessa Specialized Hospital, Ethiopia: a cross sectional study - Mulugeta Wassie; Beletech Fentie; Tseganesh Asefa (BMC, 2021)
Abstract Background The discrepancy in cervical cancer incidence between women with HIV and women without HIV is highest in low and middle-income countries. In Africa, cervical cancer is the most common cause of cancer death. As a result, HIV-infected women are 6 times more likely to develop cervical cancer than uninfected women. In addition, HIV is associated with several triggering factors for cervical cancer, including multiple sexual partners, early sexual debut, economic status and substance use. Objective To assess the prevalence and associated factors of HIV among cervical cancer patients at Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia. Methods A cross sectional study was conducted among 1057 cervical cancer patients registered from January 1, 2014 to December 31, 2018 at Oncology Center of Tikur Anbessa Specialized Hospital. A structured English version checklist was used to collect the data from patient charts. The pre coded data were entered in to EPI-data version 3.1 then exported to STATA version 14.0 for analysis. Both bivariable and multivariable regression analysis were carried out. Variables with p value < 0.05 in multivariable logistic regression were consider as significant predictors of the outcome variable. Result The prevalence of HIV among cervical cancer patients was 18.35%. HIV among cervical cancer patients was significantly associated with age group 30-39 [AOR = 2.83; 95%CI (1.27, 6.22)] and 40-49 [AOR = 2.39; 95%CI (1.07, 5.32)], employed [AOR = 2.23; 95%CI (1.46, 3.41)] and substance users [AOR = 3.92; 95%CI (2.04, 6.28)]. Conclusion This study revealed that about 18% of cervical cancer patients were HIV seropositive. HIV seropositivity was significantly increased with 30-49 age group, employed and substance users. Authors recommended that it is better to screen all HIV seropositive patients for cervical cancer and give greater attention for women with cervical cancer in the age groups of 30-49 years, employed and substance users.